Stoliczia setoiyenica, a new species of freshwater crab from southern Thailand (Crustacea: Decapoda: Brachyura: Potamidae) - Tan, Zhi Wan; Lheknim, Vachira; Ng, Peter K. L. (Zootaxa, 2023)
A new species of freshwater crab is described from southern Thailand, near the border with Peninsular Malaysia. Species of Stoliczia are characterised by their relatively flat carapace, a third maxilliped exopod that possesses no or a very short flagellum, and a conical male gonopod terminal segment that lacks or only has a very low dorsal fold. Stoliczia setoiyenica, new species, most closely resembles S. perlensis and S. kedahensis from northern Peninsula Malaysia but can be easily distinguished from congeners by differences in carapace and male gonopod morphology. Comparisons to the two known Thai Stoliczia species, S. panhai and S. ekavibhathai, are also provided for completeness.